Short Communication: Proportion faunal assemblages of carnivorous mammals in geoecological districts of Mordovia, Russia - Alexey Andreychev (Society for Indonesian Biodiversity, 2021)
Abstract. Andreychev A. 2021. Short Communication: Proportion faunal assemblages of carnivorous mammals in geoecological districts of Mordovia, Russia. Biodiversitas 22: 4625-4632. In the forest-steppe area, carnivorous mammals are represented by species of different faunistic assemblages. This circumstance makes the study region a priority since the species of which faunistic assemblages prevail is of interest. Fifteen carnivorous species have been identified in the territory of Mordovia. Among them, the family Mustelidae predominates in terms of the number of species. The species are found in all geoecological districts, but their distribution is uneven. The most notable species in the region are located in coniferous and broad-leaved forests (40%) and species widely distributed in several natural areas (40%). 13% of the total number of noted species belong to the taiga fauna types. The steppe type of fauna is represented by only 7% of the total number of recorded species. For each geoecological region, the fauna features are given, and a list of rare and exciting species is given. The forest-steppe zone to which Mordovia belongs is compared by the fauna of carnivorous mammals with other regions from three typical faunal assemblages.